Peran Komunikasi Media Sosial Yang Dibuat Perusahaan, Komunikasi Media Sosial Yang Dibuat Pengguna Terhadap Niat Beli Dimediasi Brand Passion - Livia Tamarasari Suhendra; Kurniawati Kurniawati; Duwi Mulyati; Olivia Windy; Endang Kurnia; Grade Banirohim (JURNAL ILMIAH MANAJEMEN & BISNIS, 2021)
The purpose of this study is to analyzethe effect of firm-crated social media communication on user-generated social media communication, firm-created social media communication on brand passion, user-generated social media communication on brand passion, and brand passion on purchase intention on product content. smartphones. The sampling procedure used to collect the relevant data was using a questionnaire. The study was conducted on 150 respondents as purposive sampling, and analyzed using the SEM (structural equation modeling) method. The program used in this SEM is AMOS (analysis of moment structure). The results of this study indicate that Firm-created social media communication has a positive effect on user-generated social media communication, Firm-created social media communication has a positive effect on brand passion, User-generated social media communication has no positive effect on brand passion, and brand passion has a positive effect on purchase intentions.